2013
DOI: 10.1002/pola.26868
|View full text |Cite
|
Sign up to set email alerts
|

Stable heterocumulene monomer in water; Synthesis and polymerization of (meth)acrylates having an isothiocyanate structure

Abstract: Novel methacrylate and acrylate monomers having an isothiocyanate structure, 2-isothiocyanatoethyl methacrylate (ITEMA) and 2-isothiocyanatoethyl acrylate (ITEA), were synthesized, and their radical polymerizations were examined, respectively. ITEMA and ITEA were synthesized by addition of carbon disulfide to 2-aminoethyl methacryrate or 2-aminoethyl acrylate, followed by treatment with ethyl chloroformate. Radical polymerizations of the obtained monomers (ITEMA, ITEA) were carried out methyl ethyl ketone usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…Polymer 1 was prepared from compound 6 according to the reported procedures . 2,2′‐Azobis(isobutyronitrile) (AIBN) was purchased from Wako Pure Chemical Industry (Osaka, Japan) and purified by recrystallization from methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer 1 was prepared from compound 6 according to the reported procedures . 2,2′‐Azobis(isobutyronitrile) (AIBN) was purchased from Wako Pure Chemical Industry (Osaka, Japan) and purified by recrystallization from methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported synthesis and polymerization of methacrylic, acrylic, and styrene monomers having an isothiocyanato structure, 2‐isothiocyanatoethyl methacrylate ( ITEMA , 6 ), 2‐isothiocyanatoethyl acrylate ( ITEA ), and 4‐vinylbenzyl isothiocyanate ( VBIT ) to obtain the corresponding homopolymers, poly‐ITEMA ( 1 ), poly‐ITEA, or poly‐VBIT . We examined the reactivity of isothiocyanates and found that isothiocyanate is less reactive toward water, alcohol, and carboxylic acid than the corresponding isocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the diisothiocyanates, which are less reactive toward several nucleophilic agents and more stable in ambient moisture and air atmosphere than that of the diisocyanate, can be used for the polyaddition of various diols, diamines, and dithiols as well as the diisocyanates . The polyaddition of diisothiocyanates with diols and/or diamines affords polythiourethanes and/or polythioureas, which are especially utilized as the optical materials due to high refractive index and transparency .…”
Section: Introductionmentioning
confidence: 99%
“…There are some report for the polymer bearing isothiocyanate, and the synthesis and polymerization of 4‐(isothiocyanate) styrene was reported in litaratures . This monomer can be synthesized from 4‐amino styrene by the use of CS 2 or thiophosgene which is not desirable from the environmental standpoint .…”
Section: Introductionmentioning
confidence: 99%